Multiple roles of mitochondria in aging processes - Cedikova, M; Pitule, P; Kripnerova, M; Markova, M; Kuncova, J (Physiological research, 2016)
Aging is a multifactorial process influenced by genetic factors, nutrition, and lifestyle. According to mitochondrial theory of aging, mitochondrial dysfunction is widely considered a major contributor to age-related processes. Mitochondria are both the main source and targets of detrimental reactions initiated in association with age-dependent deterioration of the cellular functions. Reactions leading to increased reactive oxygen species generation, mtDNA mutations, and oxidation of mitochondrial proteins result in subsequent induction of apoptotic events, impaired oxidative phosphorylation capacity, mitochondrial dynamics, biogenesis and autophagy. This review summarizes the major changes of mitochondria related to aging, with emphasis on mitochondrial DNA mutations, the role of the reactive oxygen species, and structural and functional changes of mitochondria.
Keywords: autofagie; Reactive Oxygen Species; Mitochondria; stárnutí; Autophagy; Aging; zvířata; oxidační stres; mitochondrie; reaktivní formy kyslíku; DNA, Mitochondrial; Humans; Oxidative Stress; mitochondriální DNA; lidé; Animals